2008
DOI: 10.1074/jbc.m710608200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Role of Plk1 in the Regulation of p73-dependent Apoptosis through Physical Interaction and Phosphorylation

Abstract: In response to DNA damage, p73 plays a critical role in cell fate determination. In this study, we have found that Plk1 (pololike kinase 1) associates with p73, phosphorylates p73 at Thr-27, and thereby inhibits its pro-apoptotic activity. During cisplatinmediated apoptosis in COS7 cells in which the endogenous p53 is inactivated by SV40 large T antigen, p73 was induced to accumulate in association with a significant down-regulation of Plk1. Consistent with these observations, Plk1 reduced the stability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 38 publications
5
62
0
Order By: Relevance
“…On the other hand, KD Plk1(K82M) did not modify the protein stability of TAp63alpha. In addition, the Plk1-related degradation of TAp63 was not attenuated by a proteasome inhibitor MG132 (data not shown), consistent with the phenomenon in TAp73/Plk1 experiments (Koida et al, 2008). These results suggest that Plk1 downregulates the protein stability of TAp63 by its phosphorylation through a proteasome-independent pathway and suppresses TAp63-induced cell death.…”
Section: Plk1 Represses Tap63-mediated Transcriptional Activationsupporting
confidence: 76%
See 3 more Smart Citations
“…On the other hand, KD Plk1(K82M) did not modify the protein stability of TAp63alpha. In addition, the Plk1-related degradation of TAp63 was not attenuated by a proteasome inhibitor MG132 (data not shown), consistent with the phenomenon in TAp73/Plk1 experiments (Koida et al, 2008). These results suggest that Plk1 downregulates the protein stability of TAp63 by its phosphorylation through a proteasome-independent pathway and suppresses TAp63-induced cell death.…”
Section: Plk1 Represses Tap63-mediated Transcriptional Activationsupporting
confidence: 76%
“…Interestingly, the previously reported p63 phosphorylation was related to protein stabilization, upregulation of activity and induction of apoptotic cell death (Westfall et al, 2005;Suh et al, 2006). This study, however, clarified that phosphorylation by Plk1 results in protein degradation and suppression of the transcriptional activity of TAp63alpha (Figure 5b), consistent with the inactivation of transcriptional activity in p53 and p73alpha (Koida et al, 2008). It can be noted that, this Plk1-related TAp63 degradation was affected by cell density of Hep3B cells (data not shown), suggesting that further analysis of p63 phosphorylation and its effect on degradation will be required in future.…”
Section: Plk1 Controls Cancer Cell Death Through Tap63supporting
confidence: 56%
See 2 more Smart Citations
“…So far, the feasible approach is to explore Plk1 inhibitor blocking its function on the cell cycle progression or the antitumor drug target including small molecules, antisense oligonucleotides, small interference (si)RNA and so on [5][6][7]. It was reported that down-regulation of PLK1 expression or function could inhibit cell proliferation, advance apoptosis, sensitize the tumor cells to the antitumor agents and inhibit tumor growth in mice [8][9][10][11][12][13][14][15]. Wonderfully, RNA interference is an effective strategy for gene silencing that directly transfected into tumor cells to knock down endogenous gene expression [6].…”
mentioning
confidence: 99%